Multiple Pathways to More Sustainable Diets: Shifts in Diet Composition, Caloric Intake and Food Waste - Wood, Sylvia L. R.; Alam, Mahbubul; Dupras, Jérôme (Frontiers in Sustainable Food Systems, 2019)
Our food choices, food production pathways and household behaviors together govern the impact that our diet has on our health as well as the environment. As the planetary population grows, there is an increasing awareness of the need to both improve the quality of our diets for health reasons and to reduce its impact on the Earth. From the consumer perspective, however, it is not always clear which healthy diet options and behaviors contribute most to reductions in our dietary footprint. In this paper we model and contrast the impact of the current American diet and three recommended diets from the 2015–2020 Dietary Guidelines for Americans on six environmental dimensions of the dietary footprint: land area required, blue water use, fertilizer application, primary energy input, ammonia emissions, and greenhouse gas emissions based on LCIA studies. For each diet we test the relative impact of a shift in diet composition, caloric intake and the reduction in food waste on the dietary footprint. We find that there are multiple pathways to significantly reduce the environmental impact of our diets. Shifts in diet composition from the current diet to a vegetarian diet had the greatest impact on reducing the dietary footprint, however, combinations of reducing caloric intake from 2,600 to 2,000 kcal/d combined with 50% reduction in food waste could achieve similar results in some cases. In line with results of other studies, we find that reducing red-meat and dairy contribute most to reducing the dietary footprint. However, recommended increases in fruits and vegetables with dietary shifts are accompanied by significant increases in blue water use. By combining a number of incremental shifts in diet composition, intake level, and food waste, significant land currently under production could be spared from production for other uses while still providing a nutritious diet for all.